2020
DOI: 10.5209/geop.69017
|View full text |Cite
|
Sign up to set email alerts
|

Centroamérica: neoliberalismo y COVID-19

Abstract: Este artículo examina la historia reciente de transformaciones políticas y económicas en Centroamérica y la forma en que esas circunstancias determinan la acción frente a la pandemia global por la COVID-19. Nuestro argumento es que en los últimos años, la región centroamericana ha vuelto a tener gobiernos conservadores y de derecha que han consolidado una reforma neoliberal cuyos resultados han sido el crecimiento de la desigualdad y la pobreza en la región. En ese marco, el impacto de la pandemia no solo será… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…(2022) identified that anxiety symptoms were directly linked to the development and maintenance of depression in nurses during the COVID‐19 pandemic, which reinforced the thinking of nursing professionals about leaving their job or profession (Côté et al., 2022). However, the prevalence rates found in this review may vary with the inclusion of other continents not represented in the sample, reinforcing that countries may present different responses in challenging situations, such as the COVID‐19 pandemic, based on factors such as low and medium income, low investment in health and scientific and technological development and fragile public health policies (Arias & Hurtado, 2020; Oliveira et al., 2020), especially in developing countries with low scientific production, making comparisons and generalisations impossible (Hossain et al., 2022). Mainly because given that the covid outlook in some regions of the world for example, Africa, were not the same across the continent, and nursing practitioners in these regions may have different outcomes with many other confounding factors which may impact their response to such a challenging situation.…”
Section: Discussionmentioning
confidence: 87%
“…(2022) identified that anxiety symptoms were directly linked to the development and maintenance of depression in nurses during the COVID‐19 pandemic, which reinforced the thinking of nursing professionals about leaving their job or profession (Côté et al., 2022). However, the prevalence rates found in this review may vary with the inclusion of other continents not represented in the sample, reinforcing that countries may present different responses in challenging situations, such as the COVID‐19 pandemic, based on factors such as low and medium income, low investment in health and scientific and technological development and fragile public health policies (Arias & Hurtado, 2020; Oliveira et al., 2020), especially in developing countries with low scientific production, making comparisons and generalisations impossible (Hossain et al., 2022). Mainly because given that the covid outlook in some regions of the world for example, Africa, were not the same across the continent, and nursing practitioners in these regions may have different outcomes with many other confounding factors which may impact their response to such a challenging situation.…”
Section: Discussionmentioning
confidence: 87%
“…Con esta política internacional del FMI y las políticas económicas impuestas por el Banco Mundial, se han socializado las deudas entre los pobres y privatizado las ganancias para esta élite, donde algunos han escalado hacia la riqueza mundial (Equipo Regional Humanitario de Oxfam en América Latina y el Caribe, 2020). Esta burguesía no ha reinvertido sus ganancias en el desarrollo del país, ni ha estimulado los empleos entre sus co-ciudadanos aun cuando la inflación ha pulverizado el poder adquisitivo de los pobres (Díaz y Viales, 2020).…”
Section: Conceptualización De La Seguridad Hugeunclassified
“…Con esta política internacional del FMI y las políticas económicas impuestas por el Banco Mundial, se han socializado las deudas entre los pobres y privatizado las ganancias para esta élite, donde algunos han escalado hacia la riqueza mundial (Equipo Regional Humanitario de Oxfam en América Latina y el Caribe, 2020). Esta burguesía no ha reinvertido sus ganancias en el desarrollo del país, ni ha estimulado los empleos entre sus co-ciudadanos aun cuando la inflación ha pulverizado el poder adquisitivo de los pobres (Díaz y Viales, 2020).…”
Section: Conceptualización De La Seguridad Hugeunclassified